The (non) determinants of Olympic success - Rewilak, J. (Journal of Sports Economics, 2021)
This paper empirically examines the determinants of Summer Olympic success during the period 1996-2016. By modifying the panel Tobit estimator using the Mundlak transform, the results find that population size and the host effect are the only statistically significant determinants of Olympic attainment. We also show that participating in front of a home crowd will stimulate athletic performance equally for each gender, but the impact of population differs between the sexes. These findings are confirmed using a hurdle estimator. This relaxes the assumption that the factors determining Olympic success are the same as those that influence the quantity of success.